Metalinguistic discourse about English on Flickr: A case study on Irish identity - Stok, María Florencia (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This paper is a case study focusing on the analysis of the relation among metalinguistic discourse, language and cultural identity. For this purpose, it examines the posts of ten Irish speakers on Flickr, an online site where users commonly share pictures with short comments. A small-scale corpus of 84 English-written utterances was collected to describe the metalinguistic discourse of users’ posts in order to ascertain links to their own perception of identity. Results demonstrate that Irish users seem to prefer online communication in English although they have developed a strong sense of individuality, which is characterized by employing traditional Irish stereotypes as positive identity markers.